Market building for postharvest technology through largescale extension efforts - Baributsa, D.; Abdoulaye, Tahirou; Lowenberg-Deboer, J.; Dabiré, C.; Moussa, B.; Coulibaly, O.; Baoua, I. (Elsevier, 2014)
The Purdue Improved Cowpea Storage (PICS) technology has been disseminated in 30,896 villages in 10different countries in West and Central Africa from 2007 to 2012. Extension and supply chain devel-opment efforts were required to make the PICS technology available to millions of farmers and otherusers. Several research and development organizations assisted in awareness building activities todevelop the market and increase access. Thousands of village and market demonstrations were imple-mented byfield technicians and supported by media activities. Supply chain development activities wereled by the private sector with some support from the project. Overall, 40e70 adults attended demon-strations in each village, among which 38% were women. Large-scale extension activities substantiallyincreased the demand for the technology and helped establish the supply chain. More than 2.4 milliontriple bags were sold in thefirst 5 years of the project. In some countries, up to 50% of bags orderedduring thefirst year were bought by farmers; even though village demonstrations had not yet beencompleted. Market building activities helped convince the private sector that there were business op-portunities in buying and selling PICS bags. Bags ordered by the private sector went from 0% in 2007 to200% in 2010, proving that it is possible to commercialize a new agricultural technology in developingcountries in a relatively short time.